Lived Experiences of Pregnant Women in Prenatal Classes and Their Influence on Antenatal Anxiety: A Phenomenological Thematic Analysis - Suryanti S; Ernasari Ernasari; Nurhidayati Nurhidayati (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2026)
Prenatal classes serve as both educational and psychosocial interventions aimed at enhancing maternal preparedness during pregnancy. This study explores the subjective experiences of pregnant women participating in prenatal classes and examines how these experiences influence antenatal anxiety. A qualitative phenomenological study was conducted at the Rappokalling Community Health Center between July and December 2025. Six participants were purposively selected based on predetermined inclusion criteria, including being in the second or third trimester of pregnancy, having attended at least four prenatal class sessions, being in stable physical condition, and demonstrating willingness to participate in in-depth interviews. Data were collected through in-depth semi-structured interviews and analyzed using thematic analysis. Four major themes emerged: (1) enhanced knowledge and understanding of pregnancy and childbirth, (2) Reduced anxiety through relaxing and coping strategies, (3) Social support as an emotional buffer, and (4) Mothers’ classes contribute significantly to maternal psychological well-being by increasing health literacy, strengthening emotional regulation, and fostering peer support. Integrating prenatal classes into routine antenatal care is recommended as effective strategy to reduce antenatal anxiety.